2015
DOI: 10.1163/21659214-90000103
|View full text |Cite
|
Sign up to set email alerts
|

Agenda Setting, Religion and New Media: The Chabad Case Study

Abstract: Theoretically grounded in agenda setting, a theory focused on the transfer of influence from communication media to a public, this paper examines the media activity of Chabad, an Ultra-Orthodox Jewish movement that is committed both to making Judaism generally accessible and to influencing public discourse. Rabbi M. M. Schneerson, the movement’s late wise and charismatic leader, undertook this dual mission in light of his conception of the theological grounds for the exploitation of mass media. Our examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…The media are as much influenced by society as society is influenced by the media, and the impact is mutual and continuous ( Vilanilam, 2005 ). Hence, religious organizations devote considerable resources to communication and education designed to show their beliefs and principles to their adherents and to take care of the salience of these beliefs and principles within the daily lives of their followers and even within the lives of a more general population ( Rashi and McCombs, 2015 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The media are as much influenced by society as society is influenced by the media, and the impact is mutual and continuous ( Vilanilam, 2005 ). Hence, religious organizations devote considerable resources to communication and education designed to show their beliefs and principles to their adherents and to take care of the salience of these beliefs and principles within the daily lives of their followers and even within the lives of a more general population ( Rashi and McCombs, 2015 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Heidi Campbell (2012), going beyond the essentialist and prescriptive approaches to media and the internet, highlighted the social and religious dimensions of media use and argued that more emphasis should be given to user's religious practices both online and offline and their interconnectedness to everyday practices. In this vein, Rashi and McCombs (2015) examining the employment of the internet by Chabad, an ultraorthodox Jewish movement, for their community outreach programs from an agenda-setting theory standpoint found that their media motivation and use came from the communities' core religious beliefs and teachings, hence the religious texts in this case. Similarly, Bellar (2017) studying the app choice among a group of Evangelical Christians found that they shifted their core religious practices from offline platforms to the mobile contexts.…”
Section: Religion Media and Identitymentioning
confidence: 99%
“…Studi tentang hubungan antara agama dan internet telah sering dilakukan karena penggunaan internet secara masif oleh orang-orang dalam beragam tradisi keagamaan. Kecenderungan ini tergambar dalam pernyataan beberapa ahli yang mengatakan "Studies on the relation between religion and the internet have become frequent because of the massive use of the internet by believers in diverse religious traditions" (Brasher, 2001;Campbell & Vitullo, 2016;Cantoni & Zyga, 2007;Cheong & Poon, 2009;Dawson, 2000;Hadden & Cowan, 2000;Nisa, 2018;Rashi & McCombs, 2015;Taylor, 2003).…”
Section: Pendahuluanunclassified